Metalloproteomic Strategies for Identifying Proteins as Biomarkers of Mercury Exposure in Serrasalmus rhombeus from the Amazon Region - de Queiroz, João Vitor [UNESP]; Cavecci-Mendonça, Bruna [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Martins, Renata Aparecida [UNESP]; de Almeida Assunção, Andrey Sávio [UNESP]; Cavallini, Nubya Gonçalves [UNESP]; dos Santos, Felipe André [UNESP]; de Magalhães Padilha, Pedro [UNESP] (My University, 2020)
This manuscript describes the results of a metalloproteomic study of mercury in samples of muscle and liver tissue of the species Serrasalmus rhombeus, popularly known as black piranha and characterised as the most voracious and aggressive predator in the Brazilian Amazon. The metalloproteomic study involved using two-dimensional electrophoresis (2D PAGE) to fractionate the proteome of the muscle and liver tissue samples, along with atomic absorption spectrometry in a graphite furnace (GFAAS) to identify mercury associated with protein SPOTs and mass spectrometry with electrospray ionisation (ESI-MS/MS) to characterise the mercury-binding proteins. The protein SPOTs characterised showed concentrations in the order of 156 mg kg−1, which ranks as the highest concentrations of mercury determined so far in metalloproteomic studies involving fish species in the Amazon region. Based on FASTA sequences of proteins characterised by ESI-MS/MS, bioinformatics studies were performed that allowed identifying nine proteins with characteristics of biomarkers of mercury exposure. Of those proteins, glutathione peroxidase stands out as an enzyme of great importance in the antioxidant defence of organisms subjected to oxidative stress caused by xenobiotics.
Keywords: 2D PAGE; ESI-MS/MS; Exposure biomarkers of Mercury; GFAAS; Mercury in Amazon fish; Metallomic studies